Profitability Variables and Bank Size Effects on Corporate Zakat: Evidence from Indonesian Islamic Banks - Muhammad Anif Afandi (International Journal of Zakat, 2019)
Islamic banks carry out their operational activities based on Islamic principles. Thus, they are not only required to pay taxes but also zakat of 2.5 percent with several conditions. Theoretically, zakat has an impact on Islamic banks larger expenditures compared to conventional banks which are not obliged to. This research examines and analyzes the extent to which profitability variables which are ROA, ROE, and BOPO, and bank size which is represented by total assets, can affect corporate zakat expenditure by Islamic Commercial Banks (BUS) in Indonesia. To do so, the Panel Vector Error Correction Model (PVECM) is used to analyze the subject matters which the period covers from 2012 to 2017. This work finds that in the short-run, all the independent variables were insignificant. However, in the long-run only ROE and BOPO which were significant. The results of the Impulse Response Function (IRF) analysis showed that the dependent variable responds to the shock of its independent variables with fluctuating and even negative trend. In addition, the results of Variance Decomposition (VDC) analysis showed that the contribution of profitability variables and bank size tended to decrease toward the formation of corporate zakat expenditure by BUS until the end of the research period. Keywords: Corporate Zakat Expenditure, Islamic Banks, Profitability, Bank Size, PVECM